Artificial Intelligence Can Bring Tens of Trillions of Rubles to the Pharmaceutical Industry - A. V. Pogrebnyak (Безопасность и риск фармакотерапии, 2023)
The computational methods presently united by the concept of artificial intelligence began to form almost at the time of the emergence of mathematics. In recent decades, artificial intelligence has gained tremendous momentum and has become actively used in various fields, including pharmacy.The use of artificial intelligence in the life cycle of a medicinal product is the topic of this interview with Andrey V. POGREBNYAK, Doctor of Chemistry and Candidate of Pharmaceutical Sciences, Head of the Information Technology Department and Professor of the Department of Physical and Colloid Chemistry of the Pyatigorsk Medical and Pharmaceutical Institute (Branch of the Volgograd State Medical University).